(untitled) (Bangladesh Journal of Medical Science, 2015)
Introduction: Maternal morbidity and mortality in India continues to remain high despite concerted efforts during the past decades. Objective of this study was to determine the prevalence and indicator of Potentially Lie Threatening Conditions (PLTC) and near miss obstetric cases at different tiers of health care. Material and Methods: A cross-sectional epidemiological study was carried out over a period of 12 months as per the WHO criteria for near miss. Probability sampling was done to systematically and randomly select health facilities i.e. two primary health centers (PHC), one community health centre (CHC) and a tertiary hospital all from Doiwala block of Dehradun, Uttarakhand, India. The study included all the women attending health-care facilities, who were pregnant, in labour, or who had delivered or aborted up to 42 days ago arriving at the facility. A convenient sampling was done (a hundred percent enumeration of eligible study subjects) for the audit. Result: A total of 937 pregnant women who accessed health care had 688 live births and 231 women had one or more of the Potentially Life Threatening Conditions (PLTC). Among them, 61 women had Severe Maternal Outcome (SMO) - 51 with maternal near-miss and 10 maternal deaths. The Severe Maternal Outcome Ratio (per 1000 live births) was 88.66. The Maternal near miss Mortality Ratio (MNM-MR) and Mortality Index (MI) were 5.1 and 16.39% respectively. Conclusion: The WHO near miss approach has been found to be an effective measure to assess quality of care in maternal health across countries including India. Bangladesh Journal of Medical Science Vol.14(3) 2015 p.254-257